Cost Effective Multi-Purpose Solar Charger Unit for Rural Development - Jana, Krishnendu; Khan, Foyjuddin; Dutta, Susovan (International Journal of Computer Sciences and Engineering, 2025)
The world is staring at a mounting energy crisis. Depletion of fossil fuels is no longer a threat, but is a harsh reality that can only be overcome by the accelerated adoption of renewable resources such as solar.Solar energy in particular presents a viable option, especially in homes. About 19706 villages in India are still un-electrified [1]. This work is about using solar energy for meeting the basic need like lighting and charging devices like mobile which is become a essential part of life. These multipurpose solar charger unit are simple, portable and ready to use devices which can be used by anyone especially in remote areas. Solar panels don’t supply regulated voltage while batteries need so for charging. Hence, an external adjustable voltage regulator is used to have the desired constant voltage. Here a 6 Volt 4.5 Am-hr battery is used as a power bank for charging the mobile and lighting a 4 W LED Solar Lantern. Protection for the circuit has been given through a Zener Diode.